Odpornost proti lezenju pri visokolegiranem kromovem jeklu pri temperaturah 650 do 800°C - Skobir, Danijela Anica (Kovine zlitine tehnologije, 1999)
The microstructure and the creep resistance at 580°C were investigated for tubes of steels X20CrMoV121 from a high pressure steam boiler after several 10000 hours of operation. The influence of long time tempering on microstructure, hardness and creep rate of the tube steels was investigated. The kinetics of carbide particle growth was assessed as well as the effect of mutual particles distance on creep rate by 100 hours tests.
Keywords: cevi; legirano jeklo; popuščanje napetosti; lezenje; mikrostuktura